معدّل انتشار و نتائج البيلة الجرثومية غير العرضية في الحمل - حسن لؤي (Latakia University Journal -Medical Sciences Series, 2019)
Introduction :Asymptomatic bacteriuria is defined as greater than 100,000 (105) organisms/ml in the urine of a person who lacks symptoms. Asymptomatic bacteriuria has been reported to be associated with adverse pregnancy outcome. Aim : The objective of the present study was to find out the prevalence of asymptomatic bacteriuria (ASB) in women attending university teaching hospital in Lattakia , and to study the effect of screening and treatment on maternal and fetal outcomes . Materials and Methods : This was a prospective study enrolled antenatal women attending the outpatient clinic or admitted to the department of obstetrics and gynecology at Tishreen University Hospital in Lattakia during the period between June 2015 – June 2016 . Antenatal women at any gestational age were screened by collecting clean catch midstream urine samples and doing routine urine analysis, culture/sensitivity and colony count. Treatment was given to all bacteriaurics according to culture and sensitivity results . Two groups were made , one with treated asymptomatic bacteriuria and other with non-asymptomatic bacteriuria patients. Both groups were followed up till delivery to note their adverse perinatal outcomes. Results : Prevalence of asymptomatic bacteriuria was 12.27%. No incidence of pyelonephritis was found. No significant adverse perinatal outcome was noted amongst patients treated for asymptomatic bacteriuria. Conclusion : Early screening and treatment of ASB when implemented helps in reducing adverse maternal outcome. مقدمة : تُعرّف البيلة الجرثومية غير العرضية (ASB) بأنّها وجود أكثر من 100 ألف (105)/م جرثوم /مل في البول لدى شخص من دون وجود أيّة أعراض . لقد تمّت الإشارة في العديد من الدراسات و التقارير إلى أنّ البيلة الجرثومية غير العرضية تترافق مع محصولٍ حمليٍّ سيّء . هدف البحث : تحديد انتشار البيلة الجرثومية غير العرضية لدى النساء الحوامل المراجعات لمستشفى التعليم الجامعي في اللاذقية , و دراسة تأثير المسح و العلاج على النتائج الحملية الوالدية و الوليدية . المواد و الطرق : إنّ هذه دراسة مستقبلية شملت السيدات الحوامل المراجعات لقسم العيادات الخارجية أو المقبولات في قسم التوليد و أمراض النساء في مستشفى تشرين الجامعي في اللاذقية في الفترة الممتدة ما بين حزيران 2015 – حزيران 2016 . تم مسح الحوامل من مختلف الأعمار الحملية من خلال أخذ عينة بول نظيفة من منتصف الرشق البولي و إجراء فحص البول الروتيني , الزرع و التحسس مع تعداد المستعمرات . تم إعطاء العلاج لجميع الحوامل مع بيلة جرثومية غير عرضية وفقاً لنتيجة الزرع و التحسس . تم تقسيم المشاركين في هذا البحث إلى مجموعتين : الأولى , مجموعة الحوامل مع بيلة جرثومية غير عرضية اللواتي تلقين العلاج و الثانية , مجموعة الحوامل دون بيلة جرثومية غير عرضية. تمّت متابعة كلتي المجموعتين حتى الولادة و توثيق النتائج الحملية و الولادية . النتائج : بلغ معدّل انتشار البيلة الجرثومية غير العرضية 12.27% . لم يتم توثيق حدوث التهاب حويضة و كلية . لم يكن هنالك فرق هام إحصائياً في معدّل حدوث النتائج السلبية للحمل بين المجموعتين . الخلاصة : يساعد المسح الباكر و العلاج للبيلة الجرثومية غير العرضية في التقليل من النتائج السيئة للحمل .